A Descriptive Study of Career Satisfaction and Professional Trajectories of Certified Midwives and Certified Nurse‐Midwives. - Jefferson, Karen; Bella, Abigail; Schechter, Suzanne; Buscarino, Lauren; Hackley, Barbara; Lichtman, Ronnie (Journal of Midwifery & Women's Health)
Introduction: The Certified Midwife (CM) credential was introduced by the American College of Nurse‐Midwives in 1996 to increase the midwifery workforce and provide an equivalent direct entry pathway to midwifery practice without prior nursing education. No research has compared the professional experiences of certified nurse‐midwives (CNMs) and CMs. This study compared the career trajectories and experiences of CNMs and CMs who graduated from the State University of New York Downstate Health Sciences University Midwifery Program between 1997 and 2019. Methods: Using a cross‐sectional design, a survey was sent to 237 alumni. The survey included items on satisfaction with chosen education pathways, role transition from student to midwife, and professional experiences. Mann‐Whitney U tests and Pearson's χ2 tests of independence were used to assess group differences. Results: Of the 237 individuals invited to participate in the survey, 131 completed the survey in sufficient detail to be included in the analysis. Participants reported similar career trajectories, satisfaction with their education preparation, measures of job performance, longevity as a midwife, and overall satisfaction with their careers. CMs were significantly more likely to express dissatisfaction with their education route, largely due to a lack of geographic mobility. CMs and CNMs experienced significantly different levels of respect from professional colleagues in their first and current or most recent positions. There were no significant differences in reported clinical competence or perceived success between groups. Discussion: This study demonstrates that CNMs and CMs have equal career success and satisfaction. Expanding the geographic mobility of CMs by expanding state licensure could enhance career satisfaction and potentially increase the number of students interested in becoming CMs. Because both the CNM and CM pathways produce qualified midwives, the American College of Nurse‐Midwives and state affiliates should continue to seek CM licensure with an identical scope of practice to CNMs in all 50 states.